The teiid lizard Tupinambis in the Miocene-Pliocene of Córdoba and Entre Ríos provinces (Argentina) - Brizuela, Santiago (2012)
The aim of this contribution is to describe the lizard material from the La Playa Formation of Córdoba (Cantera Tuclame locality) and to discuss for first time its taxonomic affinities. Also, the description of material previously nominated as an extinct lizard genus Propodinema from the Ituzaingó Formation in Entre Ríos province (cliffs along the Paraná River, near the city of Paraná) is evaluated for first time. The maxilla from La Playa Formation is here attributed to Tupinambis sp. As it cannot be referred to any species in particular, the paleoenvironmental inferences previously given by other authors are considered invalid. The material from the Ituzaingó Formation is here referred to Tupinambis sp., thus, considering invalid Propodinema. The presence of this genus in the site does not contradict the current environment in the area.